GAIN AND NOISE IN ERBIUM-DOPED FIBER AMPLIFIER (EDFA) - A RATE EQUATION APPROACH (REA) - BAO, PHUNG QUOC; SON, LE HONG (Communications in Physics, 2024)
We present a rate equation approach (REA) based on the propagation equations in single-mode Erbium-Doped Fiber Amplifiers (EDFAs). Special attention is paid to the gain and the amplified spontaneous emission (ASE) noise as functions of position including the effects of some main parameters such as pump power, signal power.